Prevalence , Diagnosis and Management of Hemorage Post Partum in Early Young Woman Under 20 Years Old and Over 35 Years Old : A Systematic Review - Triasih Amalya (International Medical Journal Corp. Ltd, 2026)
Introduction: Postpartum hemorrhage (PPH) remains the leading cause of maternal mortality globally, with maternal age extremes representing potentially vulnerable populations. This systematic review aimed to evaluate the prevalence, diagnosis, and management of PPH in women under 20 years and over 35 years of age. Methods: A systematic review was conducted following PRISMA guidelines. We screened studies based on predefined criteria including target age groups (<20 or ≥35 years), relevant outcomes (prevalence, diagnosis, management), recognized PPH definitions, and acceptable study designs. Data extraction encompassed study characteristics, age-specific prevalence, risk factors, diagnostic methods, management approaches, prevention strategies, and outcomes by age. Results: From 105 included studies, global PPH prevalence was estimated at 9.97% (95% CI: 6.90%-13.04%). Both maternal age extremes demonstrated elevated risk in a U-shaped pattern. Women ≥35 years had significantly higher PPH incidence (OR range: 1.73-4.61), with rates reaching 23-30.7% compared to 4.3-16.0% in younger women. Women <20 years showed comparable elevated risk (OR=1.73, p=0.005). Risk factors concentrated in older mothers included grand multiparity (92.5%), pre-existing diabetes (26%), and hypertensive disorders (38.6%). Diagnostic methods lacked age-specific approaches. Management strategies included uterotonics (oxytocin, misoprostol), tranexamic acid (1g IV within 3 hours), mechanical interventions (balloon tamponade success 81.3-87.9%), and surgical procedures (uterine compression sutures, artery ligation). Fertility-preserving interventions were prioritized in younger women. Multi-faceted interventions reduced PPH incidence from 14.01% to 4.90% and maternal mortality from 1,104/100,000 to 279/100,000. Discussion: The elevated PPH risk at both age extremes suggests shared pathways through uterine dysfunction and comorbidities, though mechanisms likely differ—biological immaturity and primiparity in young mothers versus accumulated comorbidities and grand multiparity in older mothers. The absence of age-specific diagnostic protocols represents a critical gap, as physiological responses to hemorrhage may vary by age. Context-dependent effectiveness of interventions (tranexamic acid, misoprostol) underscores the need for resource-stratified guidelines. Conclusion: Both young (<20) and older (≥35) mothers face significantly elevated PPH risk, warranting enhanced surveillance and targeted prevention strategies. Future research should prioritize direct age-group comparisons, mechanistic studies, and resource-stratified clinical guidelines.